PEMBELAJARAN KETERAMPILAN MENULIS DALAM MATERI MENULIS NOVEL PADA SISWA KELAS XII SMA KEMALA BHAYANGKARI 1 KABUPATEN KUBU RAYA - Khairunnisa; Adisti Primi Wulan; Arni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the process of learning novel writing skills, the obstacles faced by students, and the solutions implemented by teachers in overcoming difficulties in writing novels for grade XII students of SMA Kemala Bhayangkari 1, Kubu Raya Regency. This study uses a descriptive method with a qualitative approach. Data were obtained through observation, interviews, questionnaires, and documentation studies. The research subjects included Indonesian language teachers and grade XII students. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the process of learning to write novels is carried out through the stages of planning, implementation, and evaluation. Teachers deliver material about the elements and structure of novels, provide examples, and guide students in developing story ideas based on personal experiences. However, learning is still dominated by lecture methods so that active student participation is not optimal. The main obstacles faced by students include difficulty in developing story ideas, low vocabulary mastery, weak development of plot and characterization, and low writing motivation. In addition, limited variations in learning methods and media also contribute to the low quality of student writing. The teacher provided solutions including encouragement and motivation, intensive guidance, relevant novel examples, gradual writing exercises, and utilizing students' personal experiences as sources of story ideas. These efforts were deemed effective in helping students understand the novel writing process and increasing their writing creativity. This research is expected to serve as a reference for teachers in developing more effective, creative, and meaningful novel writing lessons.